Potensi Mikoremediasi Logam Pb dan Cd dengan Isolat Jamur Indigenous dari TPA Piyungan, Yogyakarta: Indonesia - Lathifah, Annisa Nur; Prawitasari, Diah Ayu; Asmara, Adelia Anju; Haya, Diah Aqila Fadia; Karimah, Khodijah; Wulandari, Dewi (Teknik Lingkungan Universitas Islam Indonesia, 2026)
Heavy metal pollution is a major environmental problem due to its toxicity, persistence, and potential accumulation in ecosystems. Cadmium (Cd) and Lead (Pb) are among the toxic heavy metals that can contaminate soil and groundwater, particularly due to improper waste management practices. Bioremediation using microorganisms, including fungi, has been investigated as an alternative approach for reducing heavy metal contamination. This study aimed to isolate indigenous fungi from Piyungan Landfill soil and evaluate their potential for Cd and Pb bioremediation. Soil sampels were collected from Piyungan Landfill and subjected to fungal isolation using pour plate methods to obtain indigenous fungal isolates. The remediation potential of fungal isolates was evaluated in modified nutrient-limited media supplemented with Cd concentrations of 0.5, 5, and 10 ppm and Pb concentrations of 50, 100, and 150 ppm, with Bromothymol Blue (BTB) as an indicator. Fungal characterization was performed based on macroscopic observations, including colony color, surface characteristics, and morphology, as well as microscopic observation using lactophenol blue staining. All isolates demonstrated potential for heavy metal bioremediation, indicated by fungal growth and changes in medium color and pH after exposure to Pb and Cd. The optimum remediation potential for Cd was observed in isolates 5, 6, and 7 at concentrations of 0.5, 5, and 10 ppm, respectively. Meanwhile, all isolates showed potential for Pb remediation based on changes in the test medium. These findings indicate that indigenous fungi isolated from landfill soil have potential as biological agents for the remediation of Pb- and Cd-contaminated environments.